Preparation of medium-chain-length poly-3-hydroxyalkanoates – based polymeric nanoparticle through phase inversion emulsification and its apparent formation mechanism / Khairul Anwar Ishak - Khairul Anwar, Ishak (2017)
Development of biodegradable polymeric nanoparticle for active compounds delivery into human body has gained a widespread interest in nutraceutical and pharmaceutical industries. It is frequently used as active compounds delivery vehicle due to its better encapsulation capability and controlled release, compound bioavailability improvement as well as non-toxic properties. However, common methods for polymeric nanoparticle production involve the application of polymerizing/crosslinking initiator and organic solvent, which are usually toxic and pose removal, disposal and recycling issues in the scaling up of polymeric nanoparticle production. This study demonstrated for the first time, a greener alternative for the production of polymeric nanoparticle by using medium-chain-length poly-3- hydroxyalkanoates (mcl-PHA) as part of component materials through phase inversion emulsification (PIE) method. It is a facile route to obtain polymeric nanoparticles whereby mcl-PHA serves as the integral component in the construction of protective encapsulating matrix in the nanoparticle. Emulsification process of mcl-PHAincorporated emulsion system involved the formation of bi-continuous or lamellar structure phase at emulsion inversion point (EIP) before dispersion of oil phase into nanometer-sized particles. However, incorporating mcl-PHA into the emulsion system at inappropriate molecular weight and amount would lead to an alternative phase inversion mechanism that involved the formation of multiple emulsions resulting in micrometer-sized particles with wider distribution. Temperature also showed an interaction effect with mcl-PHA molecular weight towards the formation of bicontinuous/ lamellar structure phase. Apparent formation mechanism for mcl-PHAincorporated nanoparticle is proposed based on the experimental findings.